THE URGENCY OF SPIRITUAL EDUCATION IN FACING SOCIETY PERSPECTIVE Dr. KH. SAID AQIL SIRAJ IN HIS BOOK TASAWUF AS A SOCIAL CRITICISM - Muhammad Arif Nasruddin, Qowiyudin Mulya Lubis, Hasan Bisri (PRODI PAI FIK UNIRA MALANG, 2025)
This research is based on the phenomenon that occurs in modern society, which is not only experiencing a crisis of purpose or spiritual emptiness. Therefore, the author provides his study that examines the need for spiritual education in interacting with society from the perspective of Dr. KH.Said Aqil Siraj in his book